Histomorphometric analysis of dermal collagen and elastic fibres in skin tissues taken perpendicular to each other from head and Nneck region. - Naveen K,; Pramod K,; Keerthana P,; Satheesha NB,; Ranjini K,; Raghuveer CV, (Department of Surgery, UKM Medical Centre, 2014)
To find the anatomical cause difference in scar appearance in different direction of the same region, the distribution of collagen and elastic tissue between the sections taken in two orientations perpendicular to each other from head and neck region were studied. Total of 120 skin samples taken from five different areas of head and neck region in two directions from 12 cadavers were processed and stained with special stain Verhoeff-van Gieson stain. Quantitative fractions of collagen and elastic fibres were measured by image analysis using tissue quant software Version 1.0. There was a significant differences of quantitative fractions of collagen and elastic tissue between horizontal and vertical direction in areas where skin was thick and tight (scalp and forehead with p<0.01). Relatively thinner and loose areas of skin (submandibular area, neck) showed statistically significant asymmetrical distribution of elastic tissue only (p <0.01). In very thin and loose skin (lateral canthal area), the difference in distribution of both collagen and elastic tissue was not statistically significant. Asymmetrical distribution of dermal collagen and elastic tissue in two directions of the sections in the same region could be one of the causes of difference in the appearance of scar placed in different directions of the same region.